Implementation of Social Care Character Value in Social Studies in Primary School - Marhadi, Hendri (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This study aims to gain a description of social care values in social science in elementary school applied in students action and behaviour. It uses literature review method which examines various literatures related to social care values. Character building is an effort to help someone understanding, caring, and acting based on basis of ethical values. By character building, students are expected to be able to use their knowledge, examine, internalize and personalize character and moral values, so that it can appear in daily life. Social care values are action and attitude to give a help to others and one who needs it. By social science, students are guided and improved, particularly their intellectual quotient. Those aim to make them all be citizens who have a social care character and become a part of him in behaving.